Anterior Cruciate Ligament Injuries in Athletes: Risk Factors, Mechanisms, Treatment, and Return-to-Sport Outcomes – A Narrative Review - Bednarski, Krzysztof; Kornacka, Natalia; Majewska, Melania; Piasecka, Natalia; Rafalska, Izabela; Smagoń, Jakub; Kaim, Martyna; Bober, Joanna; Bochenek, Magdalena; Siewiera, Wiktoria (Journal of Education, Health and Sport, 2026)
Background: Anterior cruciate ligament (ACL) injury is a common and serious injury in athletes, particularly in sports involving pivoting, jumping, and rapid direction changes. ACL rupture may result in knee instability, reduced performance, prolonged absence from sport, and increased risk of osteoarthritis. Aim: The aim of this study was to summarize current evidence regarding risk factors, treatment, rehabilitation, and return-to-sport outcomes after ACL injury in athletes. Materials and methods: This narrative review analyzed current literature on ACL injuries in athletes. Studies concerning epidemiology, injury mechanisms, treatment strategies, rehabilitation, and return to sport were identified using PubMed, Scopus, and Google Scholar. English-language publications from 2000–2024 were included. Results: ACL injury is multifactorial and strongly associated with neuromuscular and biomechanical deficits. Prevention programs focused on neuromuscular training may reduce injury risk. ACL reconstruction combined with structured rehabilitation remains the preferred treatment for many athletes. Criteria-based return-to-sport assessment is increasingly recommended to reduce re-injury risk. Conclusions: Effective ACL injury management requires prevention, individualized rehabilitation, and evidence-based return-to-sport decisions. Despite advances in treatment, the risk of secondary injury remains significant.